Sex, culpability, and the defence of provocation - Tyson, Danielle (Routledge, 2013)
"The partial defence of provocation is one of the most controversial doctrines within the criminal law. It has now been abolished in a number of international jurisdictions. Addressing the trajectory of debates about reform of the provocation defence across different jurisdictions, Sex, Culpability and the Defence of Provocation considers the construction and representation of subjectivity and sexual difference in legal narrations of intimate partner homicide. Undeniably, the most vexing exculpatory cultural narrative of our times is that of a woman 'asking for it'. This book explores how the process of judgment in a criminal trial involves not only the drawing of inferences from the facts of a particular case, but also operates to deliver a narrative. Law, it is argued, constructs a narrative of how the female body incites male violence. And, pursuing an approach that is informed by socio-legal studies, literary theory and feminist theories of the body, Sex, Culpability and the Defence of Provocation considers how this narrative is constructed via a range of discursive practices that position woman as a threat to masculine norms of propriety and autonomy. Once we have a clear understanding of the significance of narrative in legal decision-making, we can then formulate textual strategies of resistance to the violence of law's victim-blaming narratives by rewriting them"--Provided by publisher